(NsU^ASNA WI]A OSW)QÆTA(B: (NSWÆTOWÆ TENDENCÆÇ Æ uKRAÇNA (B:s)E (NTENDENC)QÆÇ OSWÆTI (B/s)E - (Nf)QÆNÆKOW(B, (Nt(B. (Nw(B.,s)E; )Qæ(NNSTITUT EKONOMÆKIs)E ((NkI)QÇW (B:s)E (NtAKSON(B,s, 2002)
(Nu KNIZ)QÆ ROZGLQDA@TXSQ TENDENCÆÇ ROZWITKU SU^ASNOÇ WI]OÇ OSWÆTIs)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NwI]A OSW)QÆTAs)E -- (NsW)QÆTOWÆ TENDENCÆÇs)E -- (NuKRA)QÇNAs)E; (NWI]A OSW)QÆTAs)E; (NTENDENC)QÆÇs)E; (NWZA)QÃMOWPLIWs)E; (NKRIZA OSW)QÆTIs)E; (NOSW)QÆTNQ POLÆTIKAs)E; (NADAPTIWN)QÆSTXs)E